Learning to Live Together. A Key Educational Challenge of our Time - Chang Hiang-Chu, Ausilia (Journal of Vasyl Stefanyk Precarpathian National University, 2024)
The commitment of learning to live together / with others is considered a key educational challenge of our time. A challenge that we cannot exempt ourselves from because it is an indispensable task for all, without exception. On the basis of contributions by some international organizations - in particular, UNESCO and the Council of Europe - the author focuses on the need to educate people to live together in the culture of human rights. The author presents UNESCO's permanent program Education for All as a way of living together, and considers the inclusive education, the quality education, the integral education and education to solidarity as a way forward for the future, and the intercultural education as a strategy of living together. The author concludes by highlighting that these perspectives, and so the same Education for All, must be set on the path of learning to love in order to succeed, addressing the most vulnerable segments of society, including refugees affected by war, natural disasters and poverty. This emerges as a global challenge today and a consideration absent in the already examined prospects which seems a rare consideration outside the Catholic circles. Confronted with the present circumstances, which include not only wars and organized violence but also a monumental climate catastrophe, it is now crucial to rediscover the profound essence of education and the pedagogical contemplation that enlightens educational endeavors, befitting human dignity. Undoubtedly, the prospects involve instilling the principles of living together through early childhood education, practicing democratic values, fostering serene coexistence, peace, and solidarity, while respecting and promoting the fundamental rights of all human beings. Despite the challenging situations witnessed globally, this vision may seem like an unattainable utopia, but it remains a crucial goal for the future.